PERBANDINGAN EFEKTIFITAS ANTARA MOTIVATIONAL SELF-TALK DAN INSTRUCTIONAL SELF-TALK TERHADAP AKURASI FREE THROW SHOOT ATLET BASKET FIKK UNM: THE COMPARISON OF EFFECTIVITY BETWEEN MOTIVATIONAL SELF-TALK AND INSTRUCTIONAL SELF-TALK ON THE ACCURACY OF FREE THROW SHOOT OF FIKK UNM BASKETBALL ATHLETES - Muflih Wahid Hamid (Jurnal Psikologi Jambi, 2023)
ABSTRACT Introduction This research aims to determine the difference in the effectiveness of the use of instructional self-talk and motivational self talk on the free throw accuracy of FIKK UNM basketball athletes. Method There were 20 basketball athletes (14 men, 6 women) who were FIKK UNM students and met the requirements to be the research sample. All participants were divided into two groups using the match subject ordinal pairing method based on free throw shot accuracy rankings. The data analysis technique used is the paired t test with a significance level of 0.005. Result Based on the research results, it was found that there was no significant difference between the use of instructional self-talk and motivational self-talk in increasing athletes' accuracy, but both self-talks were proven to increase athletes' shooting accuracy. Although it turned out that instructional self-talk showed a higher increase in accuracy (28.49%) than motivational self-talk (18.54%). Keywords : motivation self talk, instructional self talk, free throw shoot ABSTRAK Pendahuluan Penelitian ini bertujuan untuk mengetahui perbedaan efektifitas dari penggunaan self-talk instruksional dan self-talk motivational terhadap akurasi free throw shoot atlet basket FIKK UNM. Metode Terdapat 20 atlet bola basket (14 laki-laki, 6 perempuan) yang merupakan mahasiswa FIKK UNM dan memenuhi syarat menjadi sampel penelitian. Seluruh peserta dibagi kedalam dua kelompok menggunakan metode match subject ordinal pairing berdasarkan peringkat akurasi tembakan free throw. Teknik analisis data yang digunakan adalah uji paired t test dengan taraf signifikansi 0,005. Hasil Penelitian Berdasarkan temuan didapatkan bahwa ternyata tidak ada perbedaan yang signifikan antara penggunaan self-talk instruksional dan self-talk motivational dalam peningkatan akurasi atlet, namun kedua self-talk ini terbukti meningkatkan akurasi shooting atlet. Meski ternyata self-talk instruksional lebih memperlihatkan peningkatan akurasi yang lebih tinggi (28,49%) dibandingkan self-talk motivational (18,54%). Kata Kunci : Motivation self talk, Instructional self talk, free throw shoot.